Candida albicans: genotyping methods and clade related phenotypic characteristics - Lyon, Juliana P.; Moraes, Karen C.m.; Moreira, Leonardo M.; Aimbire, Flávio; Resende, Maria Aparecida De (Sociedade Brasileira de Microbiologia, 2010)
Several molecular methods, such as Southern blotting hybridization, Multilocus Sequence Typing, and DNA microsatellite analysis, have been employed to genotype Candida albicans. The genotype analysis allows to group strains in clades, that is, a group composed of one ancestor and its descendants. These genotype studies demonstrate that clades distribution is influenced by geographic area as well as that antifungal resistance is associated with particular clades. These findings suggested that C. albicans reproduces mainly in a clonal manner, with certain degree of DNA microevolution. Additionally, virulence factors and site of isolation have also been associated with clade specificity. The present article is a brief review about the methods used for Candida genotyping and the correlated clade systems established. Special emphasis is given to Ca3 hybridization, MLST, and Microsatellites. The present work is also focused on the phenotypic and physiological traits associated with Candida clades.
Keywords: Candida albicans; clonal reproduction; microevolution; genotyping systems; phenotypic characteristics